2013
DOI: 10.1073/pnas.1222214110
|View full text |Cite
|
Sign up to set email alerts
|

T box RNA decodes both the information content and geometry of tRNA to affect gene expression

Abstract: The T box leader sequence is an RNA element that controls gene expression by binding directly to a specific tRNA and sensing its aminoacylation state. This interaction controls expression of amino acid-related genes in a negative feedback loop. The T box RNA structure is highly conserved, but its tRNA binding mechanism is only partially understood. Known sequence elements are the specifier sequence, which recognizes the tRNA anticodon, and the antiterminator bulge, which base pairs with the tRNA acceptor end. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
126
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(142 citation statements)
references
References 44 publications
15
126
1
Order By: Relevance
“…As expected from previous in vivo experiments (14), removal of the UGG sequence in NT-box Δ(UGG) resulted in an inability to bind Cac tRNA Asn (Fig. S2C).…”
Section: Asnsupporting
confidence: 87%
See 2 more Smart Citations
“…As expected from previous in vivo experiments (14), removal of the UGG sequence in NT-box Δ(UGG) resulted in an inability to bind Cac tRNA Asn (Fig. S2C).…”
Section: Asnsupporting
confidence: 87%
“…A recent study showed that binding of tRNA to the T-box can also involve interactions between specific nucleotides of the stem I apical loop with the D-and T-loop nucleotides of the tRNA (14). These interactions were proposed to serve as a specific molecular ruler that ensures effective binding of the correct tRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first domain of a T-box (stem I) contains the specifier loop (SL) that varies in size and contains a codon-like nucleotide triplet. The SL is responsible for recognition of the bound tRNA through "scanning" of its anticodon sequence by Watson-Crick base-pairing with the tRNA anticodon (Grigg et al 2013;Zhang and Ferré-D'Amaré 2013). At the beginning of the stem I duplex, a kink turn (or K-turn) is formed.…”
Section: Introductionmentioning
confidence: 99%
“…The leader mRNA contains a codon designated the "specifier sequence" which base-pairs with the anticodon of the cognate tRNA [3] [5]. Additionally, the conserved acceptor end sequence of tRNA, NCCA where N is referred to as the discriminator base, base-pairs with a bulged region of the antiterminator (UGGN) with covariance observed between the two variable bases (N) of these sequences [4].…”
Section: Introductionmentioning
confidence: 99%